Synthesis of urea calcium phosphate via ball milling technique: article / Nur Fairuzza Syahiera Fauzi and Atikah Kadri - Fauzi, Nur Fairuzza Syahiera; Kadri, Atikah (2019)
Urea calcium phosphate, CO(NH₂)₂•Ca₃(PO₄)₂•H₂O was prepared using mixer ball mill by estimating the weight ratio of urea prills and calcium phosphate (monohydrate) powder. The structural properties and phase transformations of the synthesized substances were analysed by using Fourier Transform Infrared Spectroscopy (FTIR) and X-ray diffraction (XRD). Based on these analyses, this study suggested that urea calcium phosphate can be synthesized at 1:3 weight ratio of urea to calcium phosphate (monohydrate) at 10 minutes milling time.